(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
This paper is mainly intended for postgraduate orthodontic students especially for those who will learn and practice the Fixed Appliance Technique. With the advancement of research, introduction of new biomaterials and techniques, the orthodontic treatment has been scientifically affordable for the last few decades. In Bangladesh the orthodontic treatment and education is also becoming very popular in the private and institutional level day by day. In fact, post-graduate trainee doctors in the department of orthodontics & Dentofacial Orthopedics, Dhaka Dental College and Hospital were the once who had the idea of writing this paper. While supervising & conducting FCPS Part II examination as a convener, I felt this sort of clinical and technical review would be very helpful for the trainees as well as practitioners. Keeping that thought in my mind, I also intend to write a series of papers that will contain the basic as well as contemporary orthodontic techniques and philosophy. Post-graduate trainee doctors, faculty members and private practitioners will all find this paper as a guideline during their training as well as in professional practicing period. I am very much delighted to present this paper and series of papers in the next subsequent issues. The present paper describes training techniques, the design of standard edge-wise-technique in sequential stages for treating Angle Class II maxillary protrusion with excessive over jet, overbite (upper and lower 1st premolar extraction case), and illustrated case reports1,2 of class II malocclusion. The author acknowledges that the paper is summarized from lectures, handouts during his postgraduate studies in Kyushu University and Hiroshima University, Japan and also clinical experience acheived from the Department of Orthodontics and Dentofacial Orthopedics, Dhaka dental College and Hospital and private practice in Bangladesh. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15976 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 27-37